A CRITICAL REVIEW OF THE ROLE OF CUSTOMS IN HUMANITARIAN LOGISTICS - Koukoui Koudognonnou, Raissa Pamela Abele (2014)
The last two decades have seen significant increase in the amount of natural disasters such as earthquakes, tsunamis, floods and droughts. Human-made disasters add to the latters with crisis resulting from political instabilities such as war, terrorism, or social factors, including religious discriminations and racism. Disaster relief operations are consequently becoming very important to assist the victims of these disasters and save human lives. Logistics activities play an important part in the relief operations in ensuring that important relief supplies arrive in due time and in the right condition where they are needed. However, the management of the logistical operations in disaster settings is challenging due to various obstacles that have to be contended with. Among the obstacles are the delays encountered during clearance processes for imported relief goods which are urgently need on the field. This study focused on the investigation of the factors at the origin of delays during completion of customs formalities for relief supplies. The research performed mainly concentrated on the analysis of qualitative data sourced from humanitarian logistics literature and the Reliefweb.int. Findings from this research show that many factors associated with difficulties created by countries’ authorities but also the inefficiency of actors in charge of the logistical operations themselves lead to the delays of relief goods in customs. These factors include, bureaucratic bottlenecks, the request for high importation charges by customs authorities, complex and inflexible customs documentation requirements, the inadequacy of customs’ physical setting and lack of resource, arrival of inappropriately and/or insufficiently documented aid shipments and delays in application for duty and tax exemption certificates. Other delay factors identified involve the excessive arrival of external relief goods to the affected country and frequent customs offices closure at the affected country side or at the transiting country level. It was further recognised that efforts are being made by countries as well as international agencies such as the WCO and the UN OCHA in order to facilitate customs processes for relief goods. Some of the initiatives include regulatory guidelines developed by the international agencies to enable governments to establish laws that favour expedited customs processes, as well as concrete measures taken by countries’ authorities to help relief goods go through customs smoothly and as quickly as possible. It was however recognised that these initiatives have some limitations which do not favour the effective reaping of the benefits they are meant to offer. The present study will therefore serve as reference for humanitarian logistics specialists and other bodies interested in the efficiency of the logistical aspects of relief operations, for the understanding of the real aspects to focus on in order to avoid unnecessary delays in customs for goods that can help save millions of lives during disaster events.